2017
DOI: 10.1111/all.13368
|View full text |Cite
|
Sign up to set email alerts
|

Immunological differences between insect venom‐allergic patients with and without immunotherapy and asymptomatically sensitized subjects

Abstract: Immunological responses after stings varied in bee and vespid venom-allergic patients. In patients under VIT, sIgE and sIgG remained completely stable after sting challenges. Monitoring VIT efficacy was only possible in vespid venom allergy, and the sIgG threshold for rVes v 5 had the highest sensitivity to confirm tolerance. The BAT inhibition test was the most reliable tool to confirm tolerance on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 42 publications
1
35
0
3
Order By: Relevance
“…30The recent study by Arzt et al demonstrated higher specific/total IgE ratios in patients with clinically relevant VV allergy compared to participants with asymptomatic sensitization to VV and rVes v 5 21. Our current data likewise indicate low specific/total IgE ratios for BV and VV as well as the respective marker allergens in individuals without a history of sting-induced anaphylaxis (Figure 2).…”
supporting
confidence: 73%
See 2 more Smart Citations
“…30The recent study by Arzt et al demonstrated higher specific/total IgE ratios in patients with clinically relevant VV allergy compared to participants with asymptomatic sensitization to VV and rVes v 5 21. Our current data likewise indicate low specific/total IgE ratios for BV and VV as well as the respective marker allergens in individuals without a history of sting-induced anaphylaxis (Figure 2).…”
supporting
confidence: 73%
“…[15][16][17][18][19] This hypothesis has been critically questioned by some authors 20 and stands in some contrast to the observation that most subjects with hitherto asymptomatic sensitization to nonglycosylated recombinant Hymenoptera venom allergens tolerate deliberate sting challenges with the respective insect. 6,21 A recent study based on a cross-sectional population survey likewise suggests that sensitization to Hymenoptera venom marker allergens is common in the general population, whereas its clinical relevance might be low. 22 Other than in the study by Mos-…”
Section: Predisposing Factors For Marker Allergen-specific Sensitizmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that IgG prevents basophil activation by either intercepting antigen before it can cross‐link surface‐bound IgE or by binding to inhibitory receptors on mast cells triggering an inhibitory rather than activating signal . Other forms of immunotherapy including subcutaneous immunotherapy for bee venom and grass pollen induce an increase in IgG4 that intercepts antigen, preventing it from binding to cells. A previous study showed that peanut OIT‐induced IgG acts through the IgG receptor, FcγRII on basophils to inhibit their activation .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that an increase in the IgG/IgE ratio correlates with a reduction in the frequency of specific IgE and skin reactions in patients who have undergone at least 3 years of VIT [197]. However, no validated tests are currently able to predict venom tolerance owing to variability in immunological parameters during VIT [198].…”
Section: High Tryptase Valuesmentioning
confidence: 99%